POLA PERILAKU KOMUNIKASI GURU PEMBIMBING BELAJAR LANGSUNG PADA PENDIDIKAN INKLUSI SISWA BERKEBUTUHAN KHUSUS DI SMPN 4 PAKAN SINAYAN PAYAKUMBUH - Indah Rezqy Sanriza; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Every student needs to adapt and socialize to a wider and heterogeneous environment to enable them to adapt and socialize when they have to face different environment. The ability to adapt with a heterogeneous environment is very important to help them to get used to socialize well and affect their future time. Special needs students need special guidance from shadow teacher in order to improve their academic achievements. Therefore, the shadow teacher needs to apply appropriate communication pattern in guiding the students. The purpose of this study is to find out the communication pattern used by shadow to in SMPN 4 Pakan Sinayan Inclusive School Payakumbuh in guiding special needs students to improve the students’ academic achievements in SMPN 4 Inclusive School Payakumbuh. The researcher used symbolic interactionism and communication patterns as the theoretical basis. However, researcher are more inclined to use the communication pattern. The type of this research is a descriptive research with qualitative analysis. The technique of collecting prime data is through deep interview. Based on the result of this study, it is found that the shadow teachers use verbal and non verbal communication patterns in teaching special needs students in SMPN 4 Pakan Sinayan Inclusive School Payakumbuh. Keyword : Communication Pattern, Special Needs Students, Shadow Teacher, Inclusive School